Creative Placemaking pada Kampung Batik Semarang Studi Kasus Kelurahan Rejomulyo - Labitta Qonitah; Agus Suharjono Ekomadyo (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The thematic village-based revitalization of settlement is an application to reorganize the urban village. The development of thematic villages is formed by the creative potential of a place. Kampung Batik is a thematic villages in Semarang, which was transformed into thematic village by creative movement, This paper will discuss transformation process of Kampung Batik Semarang by creative placemaking approach. It is found, by creative placemaking perspective, Kampung Batik transformation can raise its potential. The transformation Batik was initiated by the residents as public participation for creative placemaking.  The creative movement has an impact on livability and economic development in Batik Village.